2023
DOI: 10.1177/08861099231173086
|View full text |Cite
|
Sign up to set email alerts
|

Taking Care at Work: Gender, Coping, and Anti-Violence Work During COVID-19

Abstract: COVID-19 transformed frontline anti-violence workers’ organizational routines by transitioning to virtual formats, decreasing face-to-face interactions, and shifting client needs. To address ever-changing workplace stressors, service providers adapted and/or modified coping mechanisms. In this paper, we analyze interviews with 23 anti-violence workers in the US Great Plains region, focusing on tactics used to avoid burnout and meet client needs. We discuss how workplace pace, direct-action coping practices, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Yet this historical moment seems to have intensified dynamics driven into overdrive by a knotty web of white supremacy, neoliberal capitalism, and patriarchy.Heightened vulnerabilities and an eroding capacity to withstand unrelenting changes and acceleration have occupied many pages of journals, including ours (Kim et al, 2021). Critical feminist research showed us how the pandemic disproportionately threatened the lives and well-being of Latinx immigrants (Cross & Gonzalez Benson, 2021), Latina immigrants (Cleaveland & Waslin, 2021), sex workers (Bromfield et al, 2021), intimate partner violence survivors (Heward-Belle et al, 2022), student mothers (LaBrenz et al, 2023), trafficking survivors (Namy et al, 2023, and anti-violence workers (Welch & Schwarz, 2023). Social work scholars like Stephanie Lechuga-Peña (2022) showed us how pandemic conditions disproportionately impacted the "productivity" of pre-tenure BIPOC junior women faculty.…”
mentioning
confidence: 99%
“…Yet this historical moment seems to have intensified dynamics driven into overdrive by a knotty web of white supremacy, neoliberal capitalism, and patriarchy.Heightened vulnerabilities and an eroding capacity to withstand unrelenting changes and acceleration have occupied many pages of journals, including ours (Kim et al, 2021). Critical feminist research showed us how the pandemic disproportionately threatened the lives and well-being of Latinx immigrants (Cross & Gonzalez Benson, 2021), Latina immigrants (Cleaveland & Waslin, 2021), sex workers (Bromfield et al, 2021), intimate partner violence survivors (Heward-Belle et al, 2022), student mothers (LaBrenz et al, 2023), trafficking survivors (Namy et al, 2023, and anti-violence workers (Welch & Schwarz, 2023). Social work scholars like Stephanie Lechuga-Peña (2022) showed us how pandemic conditions disproportionately impacted the "productivity" of pre-tenure BIPOC junior women faculty.…”
mentioning
confidence: 99%